Liquid Phase Exfoliated Hexagonal Boron Nitride/Graphene Heterostructure Based Electrode Toward Asymmetric Supercapacitor Application - Zheng, Xuan; Wang, Guangjin; Huang, Fei; Liu, Hai; Gong, Chunli; Wen, Sheng; Hu, Yuanqiang; Zheng, Genwen; Chen, Dongchu (Frontiers in Chemistry, 2019)
In this paper, owing to the electrostatic interaction between graphene and h-BN, a facile liquid phase exfoliation method was carried out to fabricate h-BN/graphene based van der Waals heterostructure nanocomposites without additional chemical cross-linkers. The physicochemical properties of as-prepared composites were characterized by several electron microscopic and spectroscopic measurements. The h-BN/graphene heterostructure composites were employed to use as the anodes of asymmetric supercapacitor, and exhibited exceptional capacitive performance due to their synergistic effects. It is expected that the as-prepared h-BN/graphene materials can boost scalable heterostructure electrodes in supercapacitors, and our liquid phase exfoliation method can be used for the construction of the other energy storage and electronics.